PENERAPAN KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF CONTROL UNTUK MENINGKATKAN KOMUNIKASI POSITIF PADA MAHASISWA UMK - Pulung Juliyanto; Santoso Santoso; Nur Mahardika (Universitas Muria Kudus, 2022)
This study aims to: 1) Knowing the factors of Positive Communication in UMK students. 2) Describe the application of Behavioristic Counseling with Self Control Techniques to improve Positive Communication for UMK Students. The subjects studied were UMK students in semester VIII. Methods of data collection using the method of observation, interviews and documentation. Based on the results of the study, it can be said that there are three factors that cause deviant behavior in positive communication between MIS and AS, namely socio-economic, socio-cultural and self-image. After providing counseling with a behavioristic approach with self-control techniques, the MIS research subject can overcome controlling himself in the boarding house, then the counselee will be able to apply self-control in his daily life independently without the help of a directing counselor. AS research subjects are able to control themselves not to follow their friends' quotes as a form of behavior Self-control about behavior management and counseling techniques are very appropriate to overcome deviant behavior in positive communication.